Development and Validation of an UHPLC-MS/MS Method for Quantification of DMAG in Rat Plasma and Its Application in a Preliminary Pharmacokinetic Study in Thrombocytopenia Rats - Yan Li; Yuqing Wang; Zhiqiang Zhao; Yunxia Li; Cheng Peng; Jianming Wu (Journal of Chemistry)
A preliminary study has shown that 3, 8-Di-O-methylellagic acid 2-O-glucoside (DMAG), an ellagic tannin from Sanguisorba officinalis L., has the potential in relieving thrombocytopenia. However, there is a lack of information on the pharmacokinetics of DMAG in thrombocytopenia rats. Therefore, we aimed to establish a simple, rapid, and sensitive UHPLC-MS/MS method for quantifying DMAG and study its pharmacokinetic behavior in this study. DMAG and hispidulin (internal standard, IS) were separated on an Acquity Shim-pack GIST column using 0.1% formic acid in water and acetonitrile as the mobile phase with a total run time of 5 min and gradient elution at a flow rate of 0.3 mL/min. The recovery and matrix effects of DMAG were within 94.85%–100.40% and 94.55%–102.46%, respectively. The intraday RSD and interday RSD were between 3.31% and 13.19%, accuracy RE was ≤6.69%, and stability RSD changes were 3.38%–8.78%. As for intragastric administration, with shortened Tmax (3.00 vs. 2.16 h), Cmax (25.67 vs. 35.38 ng/mL) was added for a 2 mg/kg dose after the establishment of the thrombocytopenia rat model. Relative to normal rats treated with 4 mg/kg, in thrombocytopenia rats treated with the same dose, Cmax (49.13 vs. 67.78 ng/mL), AUC(0–t) (234.60 vs. 318.17 ng·h/mL), and AUC(0–∞) (322.74 vs. 498.57 ng h/mL) increased, MRT (18.15 vs. 26.32 h) prolonged, Tmax (3.00 vs. 2.33 h) shortened, and CL/F (12746.50 vs. 8093.50 mL/h/kg) reduced. As for intravenous administration, Cmax (1679.54 ng/mL), AUC(0–t) (589.02 g·h/mL), and AUC(0–∞) (605.58 g·h/mL) were significantly increased in thrombocytopenia rats than that in normal rats (743.76 ng/mL for Cmax, 242.46 g·h/mL for AUC(0–t), and 245.19 g·h/mL for AUC(0–∞)). Vz/F and CL/F were remarkably decreased from 343196.86 to 194659.43 mL/kg for Vz/F and 8236.18 to 3326.01 mL/h/kg for CL/F with the model establishment, respectively. Overall, we successfully developed a reliable UHPLC-MS/MS method for determining DMAG levels in rat plasma. The pharmacokinetic difference could be attributed to the pathological state of the thrombocytopenia rats, which may affect the absorption, distribution, metabolism, and excretion of DMAG. These findings lay the foundation for further evaluating the clinical efficiency and safety of DMAG in the treatment of thrombocytopenia.